Perencanaan Strategi SI/TI Pada Aplikasi SEABANK Menggunakan Kombinasi SWOT DAN AHP - Ari Muhamad Imran; Anggi Farika Sari; Septia Nike Bela Sapira; Prind Triajeng Pungkasanti (Universitas Muhammadiyah Riau, 2024)
SeaBank is a digital banking service launched by Sea Group, a technology company from Singapore. SeaBank provides various digital banking services, such as money transfer, bill payment, e-wallet top-up, and investment.In a nutshell, SeaBank is a digital banking service that offers convenience and ease of use for its users. The results of the study show that the Sea Bank application has strengths in the form of competitive interest rates, user-friendly and intuitive applications, free admin fees, good service and transaction security, and rapid revenue growth. However, the Sea Bank application also has weaknesses in the form of lower daily transaction limits than Jenius, the absence of credit card features, suboptimal customer service, less diverse promo and reward programs, and a lack of innovative breakthroughs in the services provided. On the other hand, the Sea Bank application has opportunities in the form of the potential to expand online or mobile banking services, economic growth, the large number of Shopee users, the target market of millennials, and the market trend towards digital banks. However, the Sea Bank application also faces threats in the form of government regulation changes, economic uncertainty, Jenius's complete features, the potential for cyber security vulnerabilities, and changes in consumer behavior trends in using banking services. Based on the results of the SWOT analysis, the most appropriate SI/IT strategy for the Sea Bank application is to implement attractive loyalty programs, improve data security and privacy, and optimize the use of technology.